Can self‐monitoring mobile health apps reduce sedentary behavior? A randomized controlled trial. Issue 1 (26th August 2020) - Yamamoto, Kojiro; Ebara, Takeshi; Matsuda, Fumiko; Matsukawa, Tsuyoshi; Yamamoto, Nao; Ishii, Kenji; Kurihara, Takahiro; Yamada, Shota; Matsuki, Taro; Tani, Naomichi; Kamijima, Michihiro
Abstract: Objective: To examine whether the self‐monitoring interventions of a mobile health app reduce sedentary behavior in the short and long terms. Method: We designed a double‐blind randomized control trial. Participants were selected from among the staff of a medical institution and registrants of an online research firm. Forty‐nine participants were randomly assigned to either a control group (n = 25) or an intervention group (n = 24). The control group was given only the latest information about sedentary behavior, and the intervention was provided real‐time feedback for self‐monitoring in addition to the information. These interventions provided for 5 weeks (to measure the short‐term effect) and 13 weeks (to measure the long‐term effect) via the smartphone app. Measurements were as follows: subjective total sedentary time (SST), objective total sedentary time (OST), mean sedentary bout duration (MSB), and the number of sedentary breaks (SB). Only SST was measured by self‐report based on the standardized International Physical Activity Questionnaire and others were measured with the smartphone. Results: No significant results were observed in the short term. In the long term, while no significant results were also observed in objective sedentary behavior (OST, MSB, SB), the significant differences were observed in subjective sedentary behavior (SST, βint  − βctrl between baseline and 9/13 weeks; 1.73 and 1.50 h/d, respectively). Conclusions: Real‐time feedback for self‐monitoring with smartphone did not significantly affect objective sedentary behavior. However, providing only information about sedentary behavior to users with smartphones may make misperception on the amount of their subjective sedentary behavior.